KETERAWETAN ENAM JENIS KAYU DARI JAWA BARAT DAN RIAU - Krisdianto; Didik Ahmad Sudika; Ahmad Wahyudi; Mohammad Muslich (Jurnal Penelitian Hasil Hutan, 2015)
Preserving wood is one way to enhance its natural durability. The degree of wood protection achieved depends on the preservative impregnated in the wood and measured by its retention and penetration. Preservative retention is calculated based on the gravimetric system, while penetration is observed based on the colour differences after spot test. Preservative penetration pattern is observed visually and percentage is calculated conventionally. Digital image interpretation using Image-J software is one way to measure the preservative penetration. This paper studies the treatability of six wood species from West Java and Riau. Preservative penetration was interpreted both conventionally and digitally. Result shows hamirung, jaha and mahang putih wood species are classified into easy to preserve (class I), while bung bulang, pasang taritih and bira-bira wood species are classified asmediumto preserve (class II). Digital image identification provides easier, faster and more accurate in interpreting preservative penetration than the conventional method.